Efforts to Improve the Welfare of Coastal Communities in Batu Menyan Village through the Establishment and Training of Waste Banks: Upaya Peningkatan Kesejahteraan Masyarakat Pesisir Pantai Di Desa Batu Menyan Melalui Pendirian dan Pelatihan Bank Sampah - Fadila, Kurnia; Triloka, Joko; Badri, Rico Elhando; Saputra, Muhammad (LPPM Universitas Yudharta Pasuruan, 2023)
The aim of the service activities carried out is to utilize waste as an economic resource through the establishment of a Waste Bank. The method used in this community service activity uses a participatory approach with participatory rural assessment techniques. Implementation of activities is based on stages that are adapted to POAC management principles. The results of the implementation of the activities were considered achieved, this can be seen in the results of the pretest and posttest assessments. The results of the pretest and posttest of the first session regarding the Introduction to the Concept of Waste Banks and the Formation of a Waste Bank Organizational Structure showed an increase in scores with an average pretest score of 40 to 85. Improvement was also visible. from the results of the training in the second session regarding training on the Waste Bank financial management system with an average pretest score of 35 to 75. The service activities produced three outcomes, namely 1) Establishment of a waste bank with the name